2018
DOI: 10.1111/jzo.12612
|View full text |Cite
|
Sign up to set email alerts
|

Studying the sensory ecology of frog‐biting midges (Corethrellidae: Diptera) and their frog hosts using ecological interaction networks

Abstract: Investigating species interaction networks has advanced the understanding of the robustness of ecosystems, the impact of species invasions, resource partitioning and the coevolution of interacting species. Here, we present a 10-year study of the relationships between frog-biting midges (Corethrella) and their frog hosts in tropical lowland forests across northern Borneo. We use quantitative bipartite host-ectoparasite networks to explore this unusual relationship. Across northern Borneo, nine species of frog-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 56 publications
1
17
1
Order By: Relevance
“…We found a close correspondence in the relative proportions of midges captured with acoustic traps (both trap types) and those collected directly from frog hosts (JV unpublished). Similar observations were made in peatswamps of Brunei (Grafe et al, ), suggesting that acoustic traps accurately reflect true midge abundances. Other methods, for example, resting boxes (Camp, ), could additionally be included in future studies to obtain more accurate estimations of midge abundances as well as species diversity.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…We found a close correspondence in the relative proportions of midges captured with acoustic traps (both trap types) and those collected directly from frog hosts (JV unpublished). Similar observations were made in peatswamps of Brunei (Grafe et al, ), suggesting that acoustic traps accurately reflect true midge abundances. Other methods, for example, resting boxes (Camp, ), could additionally be included in future studies to obtain more accurate estimations of midge abundances as well as species diversity.…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, our preliminary analyses of midges collected directly from frogs show more pronounced host preferences, with some species showing a narrower host range than others (Virgo et al in prep.). In a recent study using ecological network analyses, Grafe et al () found both specialized and generalized midges when sampling on frogs in Borneo, suggesting that some frog species are better at avoiding being bitten by Corethrella than others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Locating their hosts primarily by auditory cues (Borkent 2008, Bernal and de Silva 2015), they are an emerging study system in studying the ecology and evolution of acoustic eavesdropping behaviour (Bernal et al 2006, Grafe et al 2008, 2018, de Silva et al 2015, Caldart et al 2016, Legett et al 2018). Their fossil record extends back to the early Cretaceous and their ancient age is reflected in their biogeography which suggests Gondwanan vicariate events (Borkent 2008, Baranov et al 2016).…”
Section: Introductionmentioning
confidence: 99%